Adaptation and evolution in marine environments : the impacts of global change on biodiversity - Amelio, Daniela; Brandt, Angelika 1961-; Christiansen, Jørgen Schou 1956-; Clark British, Melody S.; Convey, Peter; Di Prisco, Guido 1937-2019; Verde, Cinzia (Berlín : Springer, 2012)
The poles undergo climate changes exceeding those in the rest of the world in terms of their speed and extent, and have a key role in modulating the climate of the Earth. Ecosystems adapted to polar environments are likely to become vulnerable to climate changes. Their responses allow us to analyse and foresee the impact of changes at lower latitudes. We need to increase our knowledge of the polar marine fauna of continental shelves, slopes and deep sea, as identifying the responses of species and communities is crucial to establishing efficient strategies against threats to biodiversity, using international and cross-disciplinary approaches. The IPY 2007-2009 was a scientific milestone. The outstanding contribution of Marine Biology is reflected in this volume and the next one on "Adaptation and Evolution in Marine Environments - The Impacts of Global Change on Biodiversity" from the series "From Pole to Pole", making these volumes a unique and invaluable component of the scientific outcome of the IPY.
The second volume of "Adaptation and Evolution in Marine Environments - The Impacts of Global Change on Biodiversity" from the series "From Pole to Pole" integrates the marine biology contribution of the first tome to the IPY 2007-2009, presenting overviews of organisms (from bacteria and ciliates to higher vertebrates) thriving on polar continental shelves, slopes and deep sea. The speed and extent of warming in the Arctic and in regions of Antarctica (the Peninsula, at the present ) are greater than elsewhere. Changes impact several parameters, in particular the extent of sea ice; organisms, ecosystems and communities that became finely adapted to increasing cold in the course of millions of years are now becoming vulnerable, and biodiversity is threatened. Investigating evolutionary adaptations helps to foresee the impact of changes in temperate areas, highlighting the invaluable contribution of polar marine research to present and future outcomes of the IPY in the Earth system scenario.
La función de los autores fue determinada por el catalogador
Autores varían en cada volumen
Keywords: BIODIVERSIDAD -- FACTORES CLIMÁTICOS -- REGIONES POLARES; ORGANISMOS MARINOS; ORGANISMOS MARINOS -- REGIONES POLARES; ECOLOGÍA MARINA -- REGIONES POLARES; CONTAMINACIÓN MARINA -- REGIONES POLARES